2007
DOI: 10.1016/j.ahj.2007.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and dose-related effects of nebivolol in elderly patients with heart failure: Data from the Study of the Effects of Nebivolol Intervention on Outcomes and Rehospitalisation in Seniors with Heart Failure (SENIORS) trial

Abstract: Background The SENIORS trial showed that nebivolol reduced the risk of death or cardiovascular (CV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 34 publications
2
45
0
2
Order By: Relevance
“…If an ACEI is always given first, chances are that many elderly patients will not get a BB at all, or will get them only in low doses. This is an unwanted situation, since also in the elderly, it has been shown that BB reduce morbidity and mortality, and higher doses are more effective than lower doses [30,31]. Of course, a combination of an ACEI and BB should always be the goal of therapy, but the present data may help to underscore the importance of BB in the elderly.…”
Section: Discussionmentioning
confidence: 84%
“…If an ACEI is always given first, chances are that many elderly patients will not get a BB at all, or will get them only in low doses. This is an unwanted situation, since also in the elderly, it has been shown that BB reduce morbidity and mortality, and higher doses are more effective than lower doses [30,31]. Of course, a combination of an ACEI and BB should always be the goal of therapy, but the present data may help to underscore the importance of BB in the elderly.…”
Section: Discussionmentioning
confidence: 84%
“…Current guidelines do not mention weight dependence carvedilol dose with target dose range 25-50 mg bid [7]. High tolerability was reported for nebivolol in the SENIORS study [6,13]. Elderly patients are at a higher risk of side effects of BBs (mainly hypotension, bradycardia and pulmonary events); nevertheless, 68% of patients reached the target dose in the nebivolol group (68% of 65% on the drug at the end of the study).…”
Section: Resultsmentioning
confidence: 90%
“…One-third of the SENIORS population had LV EF435%, 50% were 75 years and older and 37% of patients were women. Beneficial effect of nebivolol started 6 months after the beginning of treatment, the study medication was extremely well tolerated with 68% of patients achieving target betablocker dose [13]. The high tolerability of nebivolol in the elderly patients with chronic heart failure might be explained by its unique pharmacological properties.…”
Section: Effect Of Nebivolol On Mortality In Elderly Patients With Chmentioning
confidence: 93%
“…Nebivolol decreased the combined primary outcome of death or hospitalization, but the effect on all causes of mortality was lower when compared with younger patients with systolic dysfunction. The study was not designed to evaluate separately the effects of nebivolol in patients with HFNEF 30 .…”
Section: Dobre Et Almentioning
confidence: 99%
“…The SENIORS study 30 , which involved 2,000 patients randomized to placebo and nebivolol, was the first study to evaluate the effects of nebivolol in elderly patients with HF, of which 35% presented preserved LVEF 30 . Nebivolol decreased the combined primary outcome of death or hospitalization, but the effect on all causes of mortality was lower when compared with younger patients with systolic dysfunction.…”
Section: Dobre Et Almentioning
confidence: 99%